Assembly and cooperative mechanism of the hexameric fungal plasma membrane H+-ATPase - Zi-Long You; Yue-Ran Ni; Yinggai Song; Hua Li; Kun-Zhao Liu; Le-Xuan Wang; Chao-Ran Zhao; Peng Zhao; Dan-Dan Chen; Lin Wang; Kai Wang; Pengyan Xia; et al. (Cell Reports)
Summary: The fungal plasma membrane H+-ATPase Pma1 hydrolyzes ATP to pump protons out of the cell to maintain the intracellular pH and membrane potential. Pma1 is unique among the P-type ATPases as it functions as a hexamer, although the underlying mechanism has been unclear. Here, we show that the Pma1 hexamer functions cooperatively, and the cooperativity is mediated by the domain-swapped N-terminal extension (NTE). The NTE of one Pma1 subunit binds to the nucleotide-binding domain of a neighboring subunit and, thus, couples the conformational changes of two neighboring subunits, enabling inter-subunit cooperativity of the ATPase activity by the hexamer. We further demonstrate that the NTE is essential for Pma1’s cooperative activity and physiological function. Therefore, our work suggests that Pma1 assembles a hexamer to promote a more efficient proton-pumping activity, perhaps to rapidly respond to environmental changes, and may facilitate antifungal drug development targeting Pma1.